Cascade C–N bond cleavage of amides/intramolecular amination reactions: an atom economical way to α-cabolin-4-ones. Issue 3 (11th December 2020) - Wang, Ye; Zheng, Zhong; Yuan, Yang; Wang, Mengdan; Guo, Zixia; Jiang, Yuan-Ye; Bai, Li-Ping; Li, Yanzhong
Abstract : A novel one-pot procedure for the synthesis of 2, 3-disubstituted α-carbolin-4-ones through successive C–N bond cleavage and intramolecular amination reactions involving a 1, 2-acyl migration has been developed. Abstract : An atom economical approach for the synthesis of α-carbolin-4-ones has been developed. This process was realized via a C–N bond cleavage/intramolecular amination cascade. During this process, one C–N and one C–C bond are cleaved and two C–N and two C–C bonds are formed. Mechanistic studies suggested a migrative N -cyclization process involving a carbene intermediate.